2004
DOI: 10.1158/0008-5472.can-03-2181
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of DNA Repair Genes and Risk of Glioma

Abstract: DNA repair genes play a major role in maintaining genomic stability through different repair pathways that are mediated by cell cycle control genes such as p53. We found previously that glioma patients were susceptible to ␥-ray-induced chromosomal breaks, which may be influenced by genetic variation in genes involved in DNA strand breaks, such as XRCC1 in single-strand break repair, XRCC3 and RAD51 in homologous recombination repair, and XRCC7 in nonhomologous end joining double-strand break repair. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 22 publications
12
105
1
4
Order By: Relevance
“…We have listed about 20 epidemiological studies reporting positive associations between DNA repair polymorphisms and cancer risk (Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ). Only a small proportion of studies were large (five studies were more than 500 pair cases and controls) and population based; however, some consistencies in results are apparent.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Dna Repairmentioning
confidence: 99%
“…We have listed about 20 epidemiological studies reporting positive associations between DNA repair polymorphisms and cancer risk (Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ). Only a small proportion of studies were large (five studies were more than 500 pair cases and controls) and population based; however, some consistencies in results are apparent.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Dna Repairmentioning
confidence: 99%
“…According to the inclusion and exclusion criteria, a total of nine publications with 3,752 Cases and 4,849 Controls were included in this meta-analysis (Wang et al, 2004;Kiuru et al, 2008;Liu et al, 2009;Zhou et al, 2009;Rajaraman et al, 2010;Custódio et al, 2012;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013). Among the nine studies, four studies (Zhou et al, 2009;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013) were performed in Asian populations and four (Wang et al, 2004;Kiuru et al, 2008;Liu et al, 2009;Rajaraman et al, 2010) were conducted in Caucasian populations.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among the nine studies, four studies (Zhou et al, 2009;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013) were performed in Asian populations and four (Wang et al, 2004;Kiuru et al, 2008;Liu et al, 2009;Rajaraman et al, 2010) were conducted in Caucasian populations. Five of the studies (Wang et al, 2004;Zhou et al, 2009;Rajaraman et al, 2010;Liu et al, 2012;Luo et al, 2013) were hospital-based and four (Kiuru et al, 2008;Liu et al, 2009;Custódio et al, 2012;Pan et al, 2013) were population-based. The genotype distributions in the controls were conformed to the HWE in all studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Currently, the etiology of glioma has not been completely understood. Previous studies have reported that a number of single nucleotide polymorphisms (SNPs) in DNA repair gene may modify glioma risk (Wang et al, 2004;Wrensch et al, 2005;Kiuru et al, 2008;Liu et al, 2009;Zhou et al, 2009;Rajaraman et al, 2010;Hu et al, 2011;Yosunkaya et al, 2010;Zhou et al, 2011). However, the clinical value of most glioma-associated molecular aberrations in terms of their significance as diagnostic, prognostic or predictive molecular markers has remained unclear (Batchelor et al, 2004;Ohgaki et al, 2004;Houillier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%